2018
DOI: 10.1016/j.jhep.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and the risk of hepatocellular carcinoma in patients at high risk: A nationwide nested case-control study

Abstract: In this longitudinal nationwide population-based nested case-control study, the association between statin use and the risk of HCC was investigated in Asian populations. Herein, we noted a beneficial effect of statin use on the development of HCC in the general population and individuals at high risk of HCC (i.e. those with diabetes or liver cirrhosis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 33 publications
4
65
0
1
Order By: Relevance
“…In this study, adjustment for important confounders of HCC included host factors (age and sex), severity of liver disease (cirrhosis and elevated ALT levels), viral factors (serum HBV DNA levels and antiviral therapy as a time‐dependent variable), and metabolic factors (DM, hypertension, cholesterol, and antiplatelet therapy as a time‐dependent variable). Although several observational studies, including meta‐analysis, have suggested reduced HCC risk by statin use, inhomogeneous population, variable degree of adjustment of potential confounder, and cross‐sectional designs were limitations of previous findings. Using a homogeneous cohort, rigorous adjustment of important confounders for HCC, and a cohort study design with a long‐term follow‐up period, these data provide further support for the causal relationship between statin use and HCC risk.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, adjustment for important confounders of HCC included host factors (age and sex), severity of liver disease (cirrhosis and elevated ALT levels), viral factors (serum HBV DNA levels and antiviral therapy as a time‐dependent variable), and metabolic factors (DM, hypertension, cholesterol, and antiplatelet therapy as a time‐dependent variable). Although several observational studies, including meta‐analysis, have suggested reduced HCC risk by statin use, inhomogeneous population, variable degree of adjustment of potential confounder, and cross‐sectional designs were limitations of previous findings. Using a homogeneous cohort, rigorous adjustment of important confounders for HCC, and a cohort study design with a long‐term follow‐up period, these data provide further support for the causal relationship between statin use and HCC risk.…”
Section: Discussionmentioning
confidence: 77%
“…Several observational studies have shown that statin use was associated with a reduction in the risk of HCC, and a meta‐analysis showed that statin use was associated with a 37% lower risk of HCC . However, the studies included a heterogeneous spectrum of clinical conditions, including viral hepatitis, alcoholic liver disease, and nonalcoholic fatty liver disease, and the degrees of adjustment for strong HCC risk factors, including liver cirrhosis, HBV DNA levels, and antiviral therapy, varied . Hence, the association between statin use and HCC remains elusive, especially for CHB‐infected patients, in whom these important confounders for HCC development have not been rigorously adjusted.…”
mentioning
confidence: 99%
“…A nested case‐control study from Korea in patients with newly diagnosed diabetes reported an adjusted OR of 0.36 (95% CI 0.22‐0.60) in statin users vs non‐users. Risk reduction was accentuated with an increase of cumulative defined daily doses …”
Section: Progression To Hccmentioning
confidence: 99%
“…Thus, close monitoring and education of prescribers can help to distinguish liver injury from underlying NAFLD and idiosyncratic drug‐induced liver injury. Beyond the CVD risk, statins have been attributed to a favorable effect on hepatocellular carcinoma incidence in a case‐control study, and thus their use can be beneficial from both a liver and CVD perspective. Additional measures to improve the CV risk could be the addition of omega n‐3 fatty acid supplements that were recently shown to decrease CV risk …”
Section: Discussionmentioning
confidence: 99%